The influence of varying proportions of terrestrial and marine dietary protein on the stable carbon-isotope compositions of pig tissues from a controlled feeding experiment. Issue 1 (1st January 2017) - Webb, Emily C.; Lewis, Jamie; Shain, Anika; Kastrisianaki-Guyton, Emma; Honch, Noah V.; Stewart, Alan; Miller, Bevis; Tarlton, John; Evershed, Richard P.
ABSTRACT: In recent years, it has become evident that limitations exist in our ability to meaningfully assess palaeodiet using stable isotope compositions. These limitations in part arise because many of the fundamental assumptions about tissue-diet relationships are poorly understood. In order to redress this deficiency, a controlled feeding experiment was undertaken to define the impact of terrestrial- vs. marine-derived dietary protein consumption on consumer tissue carbon isotopic compositions ( δ 13 C). Two generations of pigs were raised on one of five feeds with varying proportions of terrestrial (soy) and marine (fish meal) protein. A comprehensive range of tissues and fluids from 49 pigs was submitted for δ 13 C analysis. The observed tissue–whole diet and tissue–dietary protein carbon isotopic offsets were found to be highly dependent on the percentage of marine protein in diet. We suggest that the trend in δ 13 C offsets most likely derives from the increased routing of non-essential amino acids, especially glycine, with the increasing proportion of marine protein in the diet. These findings demonstrate that solely using bulk δ 13 C compositions not only masks considerable information about diet, but may also lead to erroneous representations of marine and terrestrial resource consumption in the past.